Quality changes of duck meat during thermal sterilization processing caused by microwave, stepwise retort, and general retort heating - Yang, Xiaoqi; Li, Yan; Wang, Peng; Luan, Donglei; Sun, Jingxin; Huang, Ming; Wang, Baowei; Zheng, Yuandong (Frontiers in Nutrition, 2022)
The quality changes of duck meat during thermal sterilization using microwave, stepwise retort and general retort heating were evaluated. Results showed that compared with stepwise retort and general retort, duck meat subjected to microwave showed significantly higher gumminess, chewiness, cohesiveness and resilience as well as glutamic acid, lysine and total amino acids. Low-field NMR revealed that the relative content of immobilized water after microwave and stepwise retort treatment was significantly higher than that after general retort treatment. The relative content of 1-octen-3-ol with characteristic mushroom aroma was significantly higher with microwave and stepwise retort heating than with general retort heating, while 2-pentyl-furan with poor taste was only detected with general retort heating. The muscle bundles subjected to microwave were neatly arranged, similar to those with no thermal sterilization. Overall, the meat quality after three thermal sterilization treatment was microwave > stepwise retort > general retort.